Lack of consensus among competency ratings of the same occupation: Noise or substance? - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2010)
Although rating differences among incumbents of the same occupation have traditionally been viewed as error variance in the work analysis domain, such differences might often capture substantive discrepancies in how incumbents approach their work. This study draws from job crafting, creativity, and role theories to uncover situational factors (i.e., occupational activities, context, and complexity) related to differences among competency ratings of the same occupation. The sample consisted of 192 incumbents from 64 occupations. Results showed that 25% of the variance associated with differences in competency ratings of the same occupation was related to the complexity, the context, and primarily the nature of the occupation's work activities. Consensus was highest for occupations involving equipment-related activities and direct contact with the public.